Importance of Second-Order Difference-Frequency Wave-Diffraction Forces in the Validation of a Fast Semi-Submersible Floating Wind Turbine Model: Preprint - Couling, A. J.; Goupee, A. J.; Robertson, A. N.; Jonkman, J. M. (National Renewable Energy Laboratory (U.S.), 2013)
To better access the abundant offshore wind resource, efforts across the world are being undertaken to develop and improve floating offshore wind turbine technologies. A critical aspect of creating reliable, mature floating wind turbine technology is the development, verification, and validation of efficient computer-aided-engineering (CAE) tools that can be relied upon in the design process. The National Renewable Energy Laboratory (NREL) has created a comprehensive, coupled analysis CAE tool for floating wind turbines, FAST, which has been verified and utilized in numerous floating wind turbine studies. Several efforts are currently underway that leverage the extensive 1/50th-scale DeepCwind wind/wave basin model test dataset, obtained at the Maritime Research Institute Netherlands (MARIN) in 2011, to validate the floating platform functionality of FAST to complement its already validated aerodynamic and structural simulation capabilities. In this paper, further work is undertaken to continue this validation. In particular, the ability of FAST to replicate global response behaviors associated with dynamic wind forces, second-order difference-frequency wave-diffraction forces and their interaction with one another are investigated.